2014
DOI: 10.1007/s11113-014-9346-5
|View full text |Cite
|
Sign up to set email alerts
|

India’s Age Structure Transition, Sectoral Labor Productivities, and Economic Growth: Evidence and Implications Based on National Transfer Accounts

Abstract: Using the new methodology of National Transfer Accounts, this paper quantifies the economic impacts of age structure transition and productivity growth rate on India's economic growth over the period 2005-2050 by formal and informal sectors. Growth effects are captured by the first demographic dividend (FDD) and distinguished by sector-specific (a) productivity age profiles, (b) relative and absolute labor productivity growth rates, and (c) population distribution for the benchmark year during 2004-2005. Empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Thus, both size and patterns of public spending policies on education by levels of education matter for India’s long-term growth due to age structure transition effects. The above approach, results and implications add to the existing knowledge in the FDD studies on India, such as, Narayana (2015).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, both size and patterns of public spending policies on education by levels of education matter for India’s long-term growth due to age structure transition effects. The above approach, results and implications add to the existing knowledge in the FDD studies on India, such as, Narayana (2015).…”
Section: Discussionmentioning
confidence: 77%
“…The authors find that during the low-growth era of 1991-1999, when the Philippines witnessed its first demographic dividend, demographic conditions improved in urban regions compared to those in rural areas and among the middle and upper classes compared to those in poor household groups. Using the same NTA technique, Narayana (2015) constructed estimates of the empirical links between India's demographic structure, labour productivity by sector, and economic growth. In this example, the author observes that the influence of the demographic dividend differs not only by area, as Abrigo et al (2016) concluded but also by the formal-informal economic sector.…”
Section: Theme 1: Age Structure Demographic Dividend and Economic Gro...mentioning
confidence: 99%
“…In this example, the author observes that the influence of the demographic dividend differs not only by area, as Abrigo et al (2016) concluded but also by the formal-informal economic sector. Narayana (2015Narayana ( ) used 2004Narayana ( -2005 base data to predict the effects of the demographic dividend from 2005 to 2050 and concluded that the beneficial shadow of a high ratio of the younger generation (the first demographic dividend) will last until 2045. Sectoral productivity and growth, on the other hand, are critical to enjoying rewards.…”
Section: Theme 1: Age Structure Demographic Dividend and Economic Gro...mentioning
confidence: 99%
“…Numerous studies have focused on the impact of changes in a country’s age structure on its macroeconomic variables such as fiscal indicators (Lee & Edwards, 2002; Narayana, 2014), economic growth (Bloom & Williamson, 1998; Bloom, Canning, Fink, & Findley, 2007; Mason, 1988; Narayana, 2015a, 2015b), savings, investments and capital flows (Domeij & Floden, 2006; Feroli, 2003; Higgins, 1998; Leff, 1969; Lindh, 1999; Mason, Lee, & Jiang, 2016).…”
Section: Review Of Related Literaturementioning
confidence: 99%